Analysis of Spelling Errors Among Students of the Department of Arabic Language Studies at Universiti Sultan Zainal Abidin: Error Analysis - Wan Mat, Wan Lisma (Al-Ḍād Journal, 2024)
Spelling has great importance and tremendous status and is the means of correcting correct writing. Despite its great importance, the problem of spelling weakness appears clearly among learners of Arabic for non-native speakers at all levels of education. Therefore, the researcher aimed to analyze spelling errors due to the presence of many obstacles and defects in the spelling skill among students of the Department of Arabic Language Studies in the second semester of the academic stage for the year 2023/2024 at Sultan Zainal Abidin University, Malaysia. To achieve this, she relied on the qualitative-analytical approach to reach the desired goal. Among its goals, she seeks to clarify the extent of students' understanding of the difference between the tied Taa and the tied Haa, and between the tied Taa and the open Taa. From the results she reached after analyzing the data, she concluded that the percentage of differentiating between the tied Taa and the tied Haa was (21.7%), and the percentage of differentiating between the tied Taa and the open Taa was (3.5%)only. Both obtained a very low percentage. Given the results mentioned; The researcher suggested that the study of spelling in Malaysia should start early, i.e. from primary school, to eliminate spelling errors to a large extent in all educational stages, while identifying their causes and developing programs to treat them in order to develop the learners’ language and their ability to write in the manner agreed upon by the language experts. Among her suggestions is also holding an annual spelling competition among students and motivating them with a certificate of appreciation. Keywords: Spelling Error Analysis - University Students